2019
DOI: 10.1074/jbc.ra118.007152
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrite supports a metabolic reprogramming in merlin-deficient Schwann cells and promotes cell survival

Abstract: Neurofibromatosis type 2 (NF2) is an autosomal-dominant disorder characterized by the development of bilateral vestibular schwannomas. The NF2 gene encodes the tumor suppressor merlin, and loss of merlin activity promotes tumorigenesis and causes NF2. Cellular redox signaling has been implicated in different stages of tumor development. Among reactive nitrogen species, peroxynitrite is the most powerful oxidant produced by cells. We recently showed that peroxynitrite-mediated tyrosine ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…Oxygen consumption rate was measured in adherent cells by extracellular flux analysis using a Seahorse XF24 or Seahorse XFe96 analyzer (Seahorse, Agilent). The oxygen consumption rate was measured in basal conditions and after the sequential addition of oligomycin (2 μM), trifluoromethoxy carbonylcyanide phenylhydrazone (FCCP, 5 μM) and antimycin A (10 μM) as previously described (Pestoni et al, 2019 ). For every test conducted, three baseline reads were taken prior to start of injections with an additional three measurements taken between injections.…”
Section: Methodsmentioning
confidence: 99%
“…Oxygen consumption rate was measured in adherent cells by extracellular flux analysis using a Seahorse XF24 or Seahorse XFe96 analyzer (Seahorse, Agilent). The oxygen consumption rate was measured in basal conditions and after the sequential addition of oligomycin (2 μM), trifluoromethoxy carbonylcyanide phenylhydrazone (FCCP, 5 μM) and antimycin A (10 μM) as previously described (Pestoni et al, 2019 ). For every test conducted, three baseline reads were taken prior to start of injections with an additional three measurements taken between injections.…”
Section: Methodsmentioning
confidence: 99%
“…However, for some decades already, H 2 O 2 is recognized to be an important signaling molecule (51,54), and even peroxynitrite, which is also a GPx substrate, has recently been shown to be a signal for proliferation in schwannomas (137). Therefore, a regulatory role of GPx1 can no longer be disregarded.…”
Section: Gpx1mentioning
confidence: 99%
“…22,23,[28][29][30][31] On the other hand, studies involving cultured breast cancer and Schwann cells in vitro, as well as knockout mouse models in vivo, have revealed that the deficiency of Nf2/Merlin resulted in a notable increase in the expression of prooxidant genes and levels of ROS, while simultaneously leading to a decrease in the expression of antioxidant genes. [32][33][34] These results indicate a positive correlation between oxidative stress and the Hippo-Nf2 signaling.…”
Section: Introductionmentioning
confidence: 65%